DECIDE - Kuznar, Wayne (MD Conference Express, 2015)
The DECIDE study demonstrates that the humanized monoclonal antibody daclizumab high-yield process is superior to interferon beta-1a on brain magnetic resonance imaging measures of disease activity in patients with relapsing-remitting multiple sclerosis, supporting previous findings of a reduction in the annualized relapse rate.